Caregivers of Black and Latino/a/x Students and School Personnel Perspectives on School‐Based SARS‐CoV‐2 Testing: Implications for Testing and Test‐to‐Stay Programs in K‐12 Schools. (12th December 2022) - Corneli, Amy; McKenna, Kevin; Dombeck, Carrie; Molokwu, Nneka; Taylor, Jamilah; Vergara, Lorraine; Benjamin, Daniel K.; Zimmerman, Kanecia O.; ,
ABSTRACT: BACKGROUND: "Test‐to‐stay" (TTS) is an effective approach for keeping students in school post‐exposure to severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2). To prepare for school‐based SARS‐CoV‐2 testing, we implemented formative research to gather perspectives on school‐based testing among school personnel, as well as caregivers of Black and Latino/a/x students given systemic racism, existing school inequalities, and the disproportionate effect of COVID‐19 on Black and Latino/a/x populations. METHODS: We conducted in‐depth interviews with caregivers of K‐12 grade Black and Latino/a/x students and focus group discussions with K‐12 school personnel. We described the forthcoming school‐based SARS‐CoV‐2 testing program and explored potential benefits and concerns, including concerns about testing‐related stigma and discrimination, particularly toward Black and Latino/a/x students, and implementation recommendations. RESULTS: Perceived testing benefits included school community reassurance and preventing school outbreaks. Concerns included potential student anxiety, classroom disruption, inaccurate results, and limited information for caregivers. Some participants mentioned that testing‐related stigma and discrimination could happen based on the testing selection process or results but not due to race or ethnicity. Participants provided numerous testing recommendations, including suggestions to prevent negative outcomes. CONCLUSIONS: Participants believed that stigma and discrimination from SARS‐CoV‐2 testing is possible, although differential treatment based on race or ethnicity was not anticipated. Participants' narratives provide support for school‐based testing and the testing component of TTS.